Obstacles and Supporting Elements in Shallot Seeds Educational Content Marketing - Yuliansyah, Dandy; Mulyaningtyas, Ratna Dewi; Askafi, Eka (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The research aims to identify the factors supporting and posing obstacles to educational content marketing on the YouTube channel Gusman Bojonegoro in promoting the sale of Nganjuk shallot seeds. Using a qualitative descriptive method, the study analyzes data from interviews, observations, and documentation involving the channel owner, nursery warehouse manager, employees, and farmers who purchase seeds. Key obstacles include variability in farmers' land, transportation costs, and ongoing educational needs, while effective communication, resource management, and strategic use of YouTube algorithms and SEO are vital for success. The study contributes to the literature by focusing on digital marketing for agricultural products, emphasizing the importance of high-quality content, influencer collaboration, and adaptability to trends for sustained engagement and growth.